Las instituciones en la administración financiera de las misiones diplomáticas de Colombia en el exterior (2018)
The diplomatic mission’s management is an important topic for the understanding of international relations, because it clarifies the mission’s internal operation, as management units of the Ministries of Foreign Affairs. In this sense, this article aims to present the role of institutions in the management of the Colombian diplomatic missions, especially with regards to their financial resources management. This, based on the principles that the missions are management units within their Ministries of Foreign Affairs, which in turn are the State’s multinational organizations that develop their foreign policy.